SMEs Performance: Fostering Innovativeness, Market Orientation, and Learning Orientation - Gromyko Bongso; Vera Dumonda Silitonga; Cliverrel Heryanto (Institute of Computer Science (IOCS), 2024)
SMEs in Indonesia continue to grow year after year, yet their death rate remains high owing to poor business performance. This research survey was distributed online to a total of 195 respondents, of which 152 matched the research criteria. The respondent data was processed using the SmartPLS application. The findings of this study indicate that there is a favorable association between market orientation, learning orientation, and innovativeness, and business performance. The findings indicate that SME owners must prioritize market orientation and learning orientation to foster innovation, which can improve SME firm performance. SME owners must understand their market orientation, including consumers and competitors.